Challenging Aging: Extending Lifespan and Improving Quality of Life with Science and Technology - Joaquim Pinto (Medical Studies and Health Journal (SEHAT), 2024)
The recent integration of gene therapy, cell therapy, and nanomedicine technologies has become a promising research focus in extending lifespan and improving quality of life in aging populations. This study aims to conduct a systematic review of the latest literature discussing the application of these three technologies in the context of aging. The research method used is a systematic analysis of articles selected from international databases such as PubMed, Scopus, and Web of Science, using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method as a guide. The results of the discussion show that the integration of gene therapy, cell therapy, and nanomedical technology has great potential in overcoming various aging problems and improving the quality of life in the elderly population. The implication of this research is the importance of continuing to develop integrated therapeutic approaches to respond to the challenges of aging, taking into account ethical, social and safety aspects in their application in clinical practice and the development of appropriate health policies.